Unhomeliness and Hybridity in Jung's Shine: Postcolonial Study - Putri Wahyuni; Pramudana Ihsan; Sri Lestari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This Present study is used a qualitative method that prioritizes information on the novel text and interpretation it into the analysis. The data was taken from a novel entitled Shine by Jessica Jung, and several journals and books as supporting data. The focus of this study is the main character in the Shine novel, Rachel Kim. This study is about postcolonialism. Rachel Kim had experienced identity issues that occurred in her life. This research aims to describe how the identity issue occurred in Rachel. An overview of the identity issues experienced by Rachel is explained in the discussion of this article. Unhomeliness and hybridity are concepts described in the phenomena that occurred to Rachel. Unhomeliness is a sense of a person caught in two cultures. Hybridity is the strategy of colonized become the part of the colonizer. Both theories analyze the identity issues experienced by the main characters in the novel. The reference used is the theory of unhomeliness and hybridity is to use the concept of Homi. K. Bhaba. Unhomeliness analysis refers to the phenomenon of racism, discrimination, and rejection of the main character. As a result, the main character got mockery jokes and physical appearance toward her. The main character was sorrowful and upset being Korean in America. Furthermore, the analysis of hybridity described in the phenomenon Rachel wants to become a K-pop star. Along with her move from America to Korea, she also got rejected in Korea. The cause of rejection in Korea was because of her American background. Even though she got treated like that, she still struggles to achieve her dream as a K-pop star. The analysis proved the hybridity phenomenon had a relationship with the cause of Rachel's unhomeliness. The result of this study was the main character hybridized her identity. The first perceived experience phenomenon by the main character is unhomeliness and the second is hybridity. Being a K-pop star is made her proud as a Korean. As well as being a K-pop star who has Korean America would make her special in the entertainment industry. Thus, Rachel's identity is not fixed but hybridized.